Vaginal Lactoferrin Administration Decreases Oxidative Stress in the Amniotic Fluid of Pregnant Women: An Open-Label Randomized Pilot Study - Trentini, Alessandro; Maritati, Martina; Rosta, Valentina; Cervellati, Carlo; Manfrinato, Maria Cristina; Hanau, Stefania; Greco, Pantaleo; Bonaccorsi, Gloria; Bellini, Tiziana; Contini, Carlo (Frontiers in Medicine, 2020)
Background: Oxidative stress (OxS) has been linked to several pregnancy-related complications. Previous studies demonstrated that lactoferrin (LF) has the ability to modulate inflammation, OxS and the immune function. Therefore, we aimed to observe whether vaginal LF administration was able to decrease OxS in the amniotic fluid (AF) of pregnant women undergoing midtrimester genetic amniocentesis. Methods: In this open-label clinical study, 60 pregnant women were divided into three groups: CONTROLS (n=20) not treated with LF; LACTO 4HRS (n=20), treated with LF 4 hours prior amniocentesis; LACTO 12HRS (n=20), treated with LF 12 hours prior amniocentesis. Thiobarbituric acid reactive substances (TBARS), total antioxidant status (TAS) and oxidative stress index (OSI) were measured in AF samples. In addition, we tested the in vitro antioxidant activity of LF on a cell line. Results: LF decreased the concentration of TBARS in the AF, although LACTO 4HRS demonstrated the lowest values compared with CONTROLS (P<0.0001). LACTO 4HRS had higher TAS and lower OSI than CONTROLS (P<0.0001 for both). In vitro, LF was effective against the oxidative challenge regardless of the time of pretreatment. Conclusion: In conclusion, LF decreased both in vivo and in vitro OxS, representing an intriguing viable clinical solution against complications of pregnancy related to inflammation and OxS. Trial registration: Clinicaltrials.gov, NCT02695563. Registered 01 March 2016 - Retrospectively registered, https://clinicaltrials.gov/show/NCT02695563.